Morphological characteristics of silver barb fish population Barbonymus gonionotus (Bleeker, 1849) from different water locations in Central Java Province - Hasan Ayyub; Agung Budiharjo; Sugiyarto Sugiyarto (Jurnal Iktiologi Indonesia, 2019)
There are population of silver barb (Barbonymus gonionotus) in Bengawan Solo River, Dengkeng River, Opak River and Gajah Mungkur Reservoir. Bengawan Solo River’s flow meet Dengkeng River’s flow while Opak River’s flow separated from the two other made an interesting phenomenon of population separability to study diversity and grouping between populations through morphological markers. The study aimed to analyze the diversity of silver barb in the Bengawan Solo River, Dengkeng River, Opak River and Gajah Mungkur Reservoir based on morphological characters. Measurement of morphological characters with morphometric methods with 14 measured morphological characters. Measurement of water chemical and physical factors include temperature, current velocity, depth, pH, dissolved oxygen and substrate. The result showed that the four distinguished morphological characteristics of the population predominantly in silver barb (B. gonionotus) were the dorsal depth, snouth length and caudal pundacle depth. Group analysis showed that silver barb population of the Bengawan Solo River had morphological characters more similar to the Dengkeng River than Opak River and Gajah Mungkur Reservoir because of the similarity of habitat and proximity of the location. Based on the most influential environmental factors is the difference in current velocity. Abstrak Populasi ikan tawes (Barbonymus gonionotus ) terdapat di Sungai Bengawan Solo, Sungai Dengkeng, Sungai Opak, dan Waduk Gajah Mungkur. Aliran Sungai Bengawan Solo bertemu dengan aliran Sungai Dengkeng sedangkan aliran Sungai Opak terpisah dari keduanya. Hal ini menjadikan sebuah fenomena keterpisahan populasi yang menarik untuk diteliti keragaman dan pengelompokan antar populasi melalui penanda morfologis. Penelitian ini bertujuan untuk menganalisis keragaman ikan tawes di Sungai Bengawan Solo, Sungai Dengkeng, Sungai Opak, dan Waduk Gajah Mungkur berdasarkan karakter morfologis. Pengukuran karakter morfologis dengan metode morfometrik dengan 14 karakter morfologis yang diukur. Pengukuran faktor fisika kimia air meliputi suhu, kuat arus, kedalaman, pH, oksigen terlarut, dan substrat. Hasil penelitian menunjukkan karakter morfologis pembeda keempat populasi tersebut yang dominan pada ikan tawes adalah tinggi sirip dorsal, panjang moncong, dan tinggi batang ekor. Analisis kelompok menunjukkan populasi ikan tawes Sungai Bengawan Solo memiliki karakter morfologis lebih mirip dengan Sungai Dengkeng daripada Sungai Opak dan Waduk Gajah Mungkur karena kemiripan habitat dan kedekatan lokasi. Faktor lingkungan yang paling berpengaruh adalah perbedaan kuat arus perairan.